Toward Defining and Measuring the Fiscal Impact of Public Enterprises. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
In many countries, the activities of public enterprises have an important fiscal impact. While the precise nature of this impact is often obscured, it is important that it be reflected in measures of overall fiscal activity. The paper is intended to raise and clarify some of the issues involved in this task.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet